Causes of the university of Cuenca´s english language and literature school´s graduates faulty pronunciation and possibe solutions - Torres Reyes, Gabriela
The English School´s goal is students achieve English proficiency, not only in academic field, but in real life; however, I´ve noticed the majority of them have deficiency in oral communication, asking me Why after having approved four years of linguistic study, they´re unable to use English competently? I based my hypotheses on students´age and enviroment. My objectives´re (1) explore the causes of this problem, and (2) find solutions to this problem. To achieve my objectives, I focused on three components of teaching-learning process, (learner-teacher-social context) with the purpose of determining the influence these components on learning of EFL. I´ve divided my work into four Chapters. Chapter One "Learning a Foreign Language;" study of nature of language compared to learning of a foreign language. I´ve also studied purposes for learning a foreign language; explaining differences between acquisition´ and learning.´ Chapter Two "Factors teaching-learning Process. Concerning students´ internal factors (attitude, motivation, aptitude, intelligence, age, personality) how these factors impact on their learning. Regarding teachers, aptitudes, attitudes, preparation, methodology, and the way they favor or hinder the students´ learning. I also analyzed how social context impacts on language learning. Chapter Three, "Factors affecting Foreign Language Learning." An overview of the most common language learning problems; problems students face learning a foreign language, and a classification of the factors affecting learning. Chapter Four, I connect theory with our reality by using the data gathering technique. A statistical analysis to demonstrate scientifically my hypotheses. The results state my conclusions and solutions